ies, degrees and appearances. Job placement processes and experience of inequality in young people (La Plata, 2013-2019) (Estudios Sociales, 2022)
This article aims to analyze the job placement processes and the configuration of unequal experiences in the labour market in young secondary school graduates in the city of La Plata, during the period 2013-2019. From a qualitative methodological perspective, we made an in-depth analysis of 78 interviews made to 18-to-24-year-old men      and      women,      as  well  as      participant      observation   records. We recovered and analyzed three dimensions that intervene in job placement processes (the place of social networks, the completion of secondary school, and the configuration of moral and interactive classifications), concluding in the importance of a multidimensional approach to social inequality in the analysis of young people's first labor experiences.
Keywords: young people; social inequality; job placement; work